Prospecção de bactérias exoeletrogênicas em sedimentos de manguezal - Oliveira, Régia Leiliana Souza (2024)
The growing global energy demand has increased the search for clean and renewable energy sources in recent decades, as an alternative to the use of fossil fuels. It is known that several bacterial strains present in the microbiota of soils and sewage have the capacity to transfer electrons to an anode, as a final electron acceptor and thus produce electrical energy, they are called exoelectrogenic bacteria. These microorganisms are the basis for the construction of microbial fuel cells (CCM) - MFC technology (Microbial Fuel Cell). Thus, the main objective of this work was to prospect and study the diversity of exoelectrogenic bacterial strains from mangrove sediments, as a basis for the development of alternative technology for the production of sustainable and efficient electrical energy. In this way, from a mangrove sediment sample, 200 bacterial strains were selected, divided into four groups: Heterotrophic (Biocathode and Bioanode) and Autotrophic (Biocathode and Bioanode), with 50 strains in each group. The strains were pre-selected according to their biofilm formation capacity and affinity for cathode and anode electrodes, isolated and subjected to Gram staining. Bacterial consortia were formed from the antagonism test and were tested according to their efficiency in synthetic sewage and electron transfer. Both heterotrophic bacteria and autotrophic bacteria were capable of producing electrical energy. The consortia were inoculated in CCM (11 days of acclimation) and showed good energy densities, with heterotrophic bacteria exhibiting production of 0.62 V (C2) and 0.64 V (C7) and autotrophic bacteria exhibiting production of 0.62 V (C2) and 0.64 V (C6). The consortia were able to maintain stable energy production, averaging 0.57 V, even in declining phases of microbial growth. The autotrophic consortiums C2 and C6 were connected in series, together with a battery and their maximum energy production was 2.70 V, enough to make a 3V LED light up. The bacteria were able to transfer electrons and generate electricity even with electrically conductive pili absent.